Paramagnetic Point Defects and Charge Carriers in PbS and CdS Nanocrystal Polymer Composites - Keeble, D; Thomsen, E; Stavrinadis, A; Samuel, I; Smith, J; Watt, A (2009)
Using electron paramagnetic resonance we identify point defects in CdS nanocrystals. A spectrum consistent with Cd vacancies in distorted sites is observed, and evidence for S vacancies is presented. Light-induced paramagnetic states attributed to defects are also detected in PbS nanocrystals. Nanocrystal shallow donor electron states are observed in CdS composites with the conjugated polymer poly[2-methoxy-5-(2-ethylhexyloxy)-p-phenylene vinylene] (MEH-PPV), and show an increased g-value compared to the bulk, which is consistent with quantum confinement. Dark state MEH-PPV polarons are observed for composites with small (3.6 nm) CdS nanocrystals. © 2009 American Chemical Society.